Exclusion, competition, and regulation in the retail loan market - Melnik, Arie; Shy, Oz (Journal of Banking & Finance, 2015)
Exclusion of borrowers from credit markets became a primary concern for regulators during the recovery from the recent recession. The paper analyzes loan-making institutions that set both interest rates and minimum credit requirements. We propose analytical measures of the degree of borrower exclusion from receiving loans. We analyze five market structures: Single lender, regulated interest rate, entry, interest rate discrimination, and highly-competitive lenders. Interest rate regulation improves total welfare relative to a single lender market. However, entry of a second lender reduces exclusion and generates higher total welfare. In the absence of fixed costs, perfect and Bertrand competition are optimal.